Life cycle assessment of a hot-pressing machine to manufacture particleboards: hotspots, environmental indicators, and solutions - Lopes Silva, Diogo Aparecido; Firmino, Alessandro Silveira; Ferro, Fabiane Salles; Christoforo, Andre Luis; Leite, Florence Rezende [UNESP]; Rocco Lahr, Francisco Antonio; Kellens, Karel (Springer, 2020)
Purpose Green manufacturing (GM) is the environmental benign manufacturing of products with a minimal negative impact on the natural environment. Research studies on GM have increased in the last years with attention to the application of life cycle assessment (LCA). However, the manufacturing industry still faces some barriers and challenges that hinder a proper practical integration of GM using LCA. Accordingly, this paper performs an LCA-based GM case study of a wood-based industry that produces particleboards to investigate environmental hotspots and suggests GM indicators and solutions for a hot-pressing machine tool. Methods A case study of a wood-based industry that produces particleboards in Brazil was designed. A LCA-based GM framework was developed and applied according to its three phases: pre-assessment, environmental assessment and monitoring, and post-assessment. Each phase is composed of specific stages and each stage has its own activities and goals. To quantify the environmental life cycle impacts, the ILCD midpoint method with 13 impact categories was selected. Based on these environmental impacts, a set of indicators and solutions was designed to improve the product life cycle impacts through a greener manufacturing process of particleboards. A cradle-to-grave approach was used to model the particleboard life cycle and the manufacturing phase was modeled based on the unit process life cycle inventory (UPLCI) methodology. Results and discussion The particleboard manufacture was designed into five unit processes and results of the pre-assessment showed that the hot-pressing unit was the most relevant process because of its direct and indirect impacts mainly to human toxicity cancer effects, global warming, and photochemical ozone formation. During the environmental assessment and monitoring phase, the hot-pressing machine was then investigated based on the main contributors to the caused environmental impacts, i.e., electricity consumption and air emissions of free formaldehyde, as well as in terms of its most relevant process parameters: pressure (P) and temperature (T). Opportunities to reduce up to 21% upstream impacts and up to 41% downstream impacts were identified from making simple changes to the hot-pressing parameters. Further investigation in the post-assessment revealed that environmental impacts can be estimated based on the appliedPandTvalues and GM indicators were suggested. Conclusions The proposed GM framework can be used in other case studies to integrate GM + LCA in practice. Results of the case study application showed that the hot-pressing machine was a hotspot into the cradle-to-grave life cycle impacts of particleboards and the proposed GM indicators can be used to predict life cycle impacts at manufacturing level.
Keywords: Green manufacturing of particleboards; Green manufacturing indicators; Assessment criteria and indicators; Life cycle assessment of manufacturing